2009
DOI: 10.1371/journal.pone.0005821
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 Pathway Mediates Amplification of Metastatic Potential and Resistance to Therapy

Abstract: BackgroundTraditionally IFN/STAT1 signaling is connected with an anti-viral response and pro-apoptotic tumor-suppressor functions. Emerging functions of a constitutively activated IFN/STAT1 pathway suggest an association with an aggressive tumor phenotype. We hypothesized that tumor clones that constitutively overexpress this pathway are preferentially selected by the host microenvironment due to a resistance to STAT1-dependent cytotoxicity and demonstrate increased metastatic ability combined with increased r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(96 citation statements)
references
References 60 publications
5
91
0
Order By: Relevance
“…Constitutive high expression of IFN/STAT1-regulated genes protected tumor cells from the cytotoxic effect of cisplatin and fludarabine (46,47). In human head and neck squamous, radiation-resistant tumors overexpressed a substantial number of genes inducible by IFNs or related to their signaling pathway (48)(49)(50). The IFN-related DNA damage resistance signature was also associated with resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutive high expression of IFN/STAT1-regulated genes protected tumor cells from the cytotoxic effect of cisplatin and fludarabine (46,47). In human head and neck squamous, radiation-resistant tumors overexpressed a substantial number of genes inducible by IFNs or related to their signaling pathway (48)(49)(50). The IFN-related DNA damage resistance signature was also associated with resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell numbers before and after the treatment were determined by generating standard curves with known numbers of nontreated cells. An IC 50 value was calculated based on the viability curve. The multiple drug effect analysis of Chou and Talalay (24) was used to determine the pharmacologic interaction between 5-AZA-dC and HDAC inhibitors.…”
Section: Viability Assaymentioning
confidence: 99%
“…Previous studies showed that Stat1 mediates the expression of a set of IFNinducible genes known as IFN-related DNA damage-resistance signature, which renders different tumor types increasingly resistant to chemotherapy and radiation therapies (62)(63)(64)(65). More recent work demonstrated that unphosphorylated Stat1 mediates the induction of genes that protect cells from virus infection or DNA damage in response to prolonged treatment with IFN-β (2).…”
Section: Stat1 Protects Cells From the Antiproliferative Effects Of Amentioning
confidence: 99%
“…In the nucleus, STAT1 binds to the cognate transcriptional elements and activates IFN-inducible genes, leading to growth arrest and cell death [23,24]. On the other hand, STAT1 overexpression is associated with tumor progression [25,26] and acquisition of RT resistance [19,25,27,28]. Khodarev et al reported that RT-resistant squamous cell carcinoma (SCC) cells overexpressed STAT1 [27] and suppression of STAT1 recovered RT sensitivity [28].…”
Section: Discussionmentioning
confidence: 99%